Heat-shrinkable moulded shapes. Specification requirements for shape dimensions, material requirements and compatibility performance. Heat-shrinkable elastomeric moulded shapes, semi-rigid, material requirements and system performance Part 3-102, (28th February 2011) - British Standards Institution,
No abstract available